Trauma-Focused Acceptance & Commitment Therapy untuk Meningkatkan Kesejahteraan Psikologis Perempuan Dewasa Pasca Trauma Pelecehan Seksual - Basyarahil, Marwa (Universitas Airlangga, 2024)
TF-ACT-based intervention, which targets experiential avoidance can be applied to individuals with trauma. This case report was conducted via teleconsulting using a video-conference platform with five sessions for a 25-year-old woman who experienced PTSD symptoms due to sexual violence committed by her father. This intervention aimed to help the patient improve her psychological well-being by accepting of the past, increasing awareness of the present, and preparing for the future. Based on the comparison of pre- and post-intervention GAF scores, clinical observation by the therapist, and subject’s self-report, the TF-ACT intervention was found to be effective in addressing trauma symptoms in this context. The participant could manage negative emotions that arise due to traumatic memories, more connected to the present, and had clear life goals based on their values. The future application of TF-ACT would be better if quantitative and qualitative approaches were combined to measure the effectiveness of the intervention.